Vadba pri osteoporozi - Kvas, Miha (Šport (Ljubljana), 2024)
The purpose of the article was to review and analyze all important recent literature on exercise in osteoporosis and highlight important findings that may be useful for current use in further research. Osteoporosis, often called the »silent disease«, is a condition characterized by weakened bones, leading to an increased risk of fractures. It primarily affects older adults, especially postmenopausal women. While medications and nutritional strategies are very important in managing this condition, exercise plays a key role in both the prevention and management of osteoporosis. Engaging in regular physical activity does not strengthen bones, but improves balance and coordination, which reduces the risk of falling. By understanding the benefits of exercise, individuals can be reminded to take proactive steps to maintain bone density and protect their future health.
Keywords: active aging; aging; aktivno staranje; bones; elderly; exercise; fractures; kosti; osteoporosis; osteoporoza; sport; staranje; starostnik; šport; vadba; zlomi